PENGARUH REBUSAN DAUN BINAHONG (ANREDERA CORDIFOLIA) TERHADAP KADAR GULA DARAH PENDERITA DIABETES MELITUS TIPE 2 - Handayani, Fitri; Hasneli, Yesi; Utami, Gamya Tri (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022, 2022)
Diabetes mellitus (DM) is a chronic disease that occurs when the body does not get proper use of insulin or the pancreas does not produce enough insulin. High blood sugar levels will be a thing that must be considered for people with DM if prevention and treatment are not carried out. One of the herbal plants that can be used as traditional medicine for the treatment of diabetes mellitus is Binahong. The purpose of this study was to determine the effect of binahong leaf decoction on blood sugar levels in patients with type 2 diabetes mellitus. This type of research was a quasi-experimental design with one group pretest posttest design. This research was conducted at the Rejosari Health Center. The research sample was 15 people using the purposive sampling technique who were given binahong leaf decoction for 4 consecutive days who were checked for blood sugar before consuming the stew (pretest) and 2 hours after consuming the stew (posttest). Analysis of the data used in this study is the dependent T test. The results showed that there was an effect of giving binahong leaf decoction on blood sugar levels with p-value (0,000) < alpha (0,05). There is an effect of steeping the stew of binahong leaves on the blood sugar levels of people with diabetes mellitus in the working area of ??the Pekanbaru Rejosari Health Center. Research on giving binahong leaf decoction to diabetics is very effective because binahong leaves contain compounds that can lower blood sugar levels such as saponins, flavonoids and alkaloids, so that blood sugar levels in diabetics can go down by consuming one of these herbal medicines.